STRATEGI SATUAN LALU LINTAS POLISI RESORT PONTIANAK KOTA DALAM MENGURANGI KECELAKAAN LALU LINTAS DI KOTA PONTIANAK - Dedi E.01107024 (FISIP Universitas Tanjungpura, 2013)
This thesis writing is aimed to convey a description about internal factor and external factor analysis of traffic police corps of police quarter (Polresta) in Pontianak city as well as to determine alternative strategy in reducing traffic accident of riders. Traffic problem in Pontianak is getting more and more complicated. One of the problems is traffic accident (Lakalantas).Along with economic growth and increasingly population and its’ harmony with a rise of need and ability to purchase personal and public transportation, traffic accident in Pontianak is getting more increased each year. Generally, traffic accident problem in Pontianak may be caused by both of transportation facilities and the vehicles as well as other supporting facilities that are still not able to bear the amount of vehicle. In addition, it is not less important to have a look at riders and drivers’ discipline which is one of the biggest contribution of each traffic accident because most of cases are begun with traffic rules breaking. Key Words : Transportation, Alternative Strategy, Internal Environment, External Environment, Traffic Accident.